the Initiation of Direct Contact Heat Exchanger Addition at the Evaporation Station of the X Sugar Mill - Intan Permata Sari, Hanifah Madriyah; Hasannah, Cintiya Septa (Barometer, 2024)
White crystal sugar is one of the plantation commodities that is widely produced because it is widely consumed by the people of Indonesia. White crystalline sugar at Sugar X Factory is made from sugarcane sap which has gone through the refining stage into clear sap and then concentrated using an evaporator to become thick sap, where thick sap will become white crystalline sugar after crystallization. In the process of converting clear sap into viscous sap, it requires quite a lot of steam in the evaporator, causing the used steam in the Sugar Factory to be consumed more by the Evaporation Station. In fact, in the Sugar X factory, many steam has not been able to thicken the clear sap to the maximum due to the considerable workload. This is because the incoming temperature is very low, so the temperature must be raised in order to reach the flash point to evaporate. A direct contact heat exchanger equipment needs to be installed before entering the evaporator at the Evaporation Station of the X Sugar Factory. The purpose of this research is to obtain a direct contact heat exchanger or DCHE design which will then be installed at the X Sugar Factory Evaporation Station. To obtain the desired direct contact heat exchanger design, actual data, literature data, and assumption data are needed. Based on calculations, this DCHE has an outer diameter of 1,062 meters with a height of 8,628 meters. Based on calculations, this DCHE has an outer diameter of 1,062 meters with a height of 8,628 meters. After calculation, it was found that this tool can save used steam consumption as much as 14,467 tons / hour and can increase the capacity of the tool from 5,622 TCD to 6,371 TCD, so that this equipment is considered feasible in terms of economy and use for use as a preheater before entering the evaporator of the Evaporation Station.